The effects of acid application on the dentine surface smear layer: an S.E.M. study - (:unkn) unknown (My University, 1990)
In this study, the effect of citric acid and LIV CENERA Liquid (40% poly-acrylic acid) on the smear layer of the dentine surface was investigated. Twelve freshly extracted, non-carious human molar teeth were used and approximately 25 mm2 flat occlusal dentine surfaces were prepared. Citric acid and LIV CENERA Liquid were applied for 10 and 30 seconds to the dentine surfaces. The results of our study indicated that: 1. Conditioning with LIV CENERA Liquid for 10 seconds was not effective in removing the smear layer on the dentinal tubules but application for 30 seconds was partially effective. 2. Although 10 seconds application of citric acid was not effective in removing the smear layer, 30 seconds application removed it completely, but harmful effects were observed on the dentinal tubules. 3. Conditioning with citric acid is more effective than the application of LIV CENERA Liquid in removing the smear layer, but LIV CENERA Liquid in contrast to citric acid application, did not enlarge the dentinal tubules.
Keywords: Humans; Microscopy, Electron, Scanning; Smear Layer; Acrylic Resins; Molar; Dentin; Polycarboxylate Cement; Acid Etching, Dental; Citrates; Citric Acid